Asymmetric assembly of high-value α-functionalized organic acids using a biocatalytic chiral-group-resetting process - Wei Song (Nature Portfolio, 2018)
Alpha-functionalized organic acids are building blocks of many bioactive compounds. Here, the authors developed a toolbox-like, modular set of enzymes that reset chiral groups, turning achiral glycine and simple aldehydes into stereodefined α-keto acids, α-hydroxy acids, and α-amino acids.